The Role of Civic Education Teachers in Increasing the Sense of Nationalism in Elementary School Students - Maqfira (International Journal of Students Education, 2024)
Nationalism is a noble value of Pancasila that needs to be possessed by students as the next generation of the nation to fill independence and be able to contribute to the country so that the character of students who can be competitive and resilient in the midst of the era of globalization can be realized. The purpose of this study is to determine the role of civic education teachers in increasing the sense of nationalism in elementary school students. The method used in this study is the literature review research method. Data collection techniques are carried out by studying literature from various sources such as books, journals and others. The results of the study obtained indicate that the role of civic education teachers is very important in increasing the attitude of nationalism in elementary school students, namely Civic education teachers as mentors, PPKn teachers as bridges between generations, Civic education teachers as Stimulus of creativity and Civic education teachers as Authorities. While the forms of Nationalism attitudes in elementary school students are as follows: Nationalism attitudes in terms of being proud to be Indonesian, Nationalism attitudes in terms of being willing to sacrifice, Nationalism attitudes in terms of accepting diversity and Nationalism attitudes in terms of appreciating the services of heroes.